Estrés oxidativo y patogenia del daño articular en equinos - Galleguillos, Marco; Lemaitre, Maximiliano; Letelier, María; Adarmes, Héctor (Avances en Ciencias Veterinarias, 2007)
This review describe the sinovial joint and the different structures that are present in the pathogenesis of joint disease, such as synovial membrane, articular cartilage, and synovial fluid. Oxidative stress is involved in the pathogenesis and leads to increased risk for osteoarthritis by damaging many component of the joint, so there are different antioxidants mechanism, enzymatic and not enzymatic, that inhibit joint damage. Hyaluronic acid, chondroitin-sulfate and glutathione-transferases are described as antioxidant molecules present in synovial fluid.